2009
DOI: 10.1590/s1806-83242009000400013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of breast- and bottle-feeding duration on the age of pacifier use persistence

Abstract: This study evaluated the effect of breast-and bottle-feeding duration on the age of pacifier use persistence. Questionnaires (n = 723) with information on nutritive and nonnutritive sucking habits of children aged 3-6 years were assessed. The sample was divided according to breastfeeding duration: G1 -non-breastfed, G2 -up to 3 months, G3 -discontinued between 4 and 6 months, G4 -discontinued between 7 and 12 months, and G5 -longer than 12 months. The children were also assigned to 4 groups by age of pacifier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
3
16
1
3
Order By: Relevance
“…8 Several authors have pointed out that bottle-fed children have a strong tendency to develop a pacifier-sucking habit. [9][10][11][12] Nutritive and nonnutritive sucking habits, namely bottle feeding and pacifier use, are associated to an atypical swallowing pattern, with tongue thrusting, which may be related to the development of malocclusions such as posterior crossbite. 5,7 However, while some authors have focused on the relationship between pacifier use and malocclusion in the primary dentition, 13,14 the degree of association between bottle feeding and the prevalence of occlusal alterations in the sagittal plane is still subject to conjecture.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…8 Several authors have pointed out that bottle-fed children have a strong tendency to develop a pacifier-sucking habit. [9][10][11][12] Nutritive and nonnutritive sucking habits, namely bottle feeding and pacifier use, are associated to an atypical swallowing pattern, with tongue thrusting, which may be related to the development of malocclusions such as posterior crossbite. 5,7 However, while some authors have focused on the relationship between pacifier use and malocclusion in the primary dentition, 13,14 the degree of association between bottle feeding and the prevalence of occlusal alterations in the sagittal plane is still subject to conjecture.…”
Section: Introductionmentioning
confidence: 99%
“…The study groups were established based on previous research, which indicated a beneficial influence of breastfeeding without the use of artificial nipples on occlusion; 15 which recommended nonnutritive sucking habit cessation at 2 or 3 years of age, 13,14 and which demonstrated that bottle feeding is discontinued at a higher frequency between 3 and 4 years of age. 9 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations